1996
DOI: 10.1577/1548-8675(1996)016<0473:eoteco>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Electrofishing Currents on Captive Ripe Razorback Suckers and Subsequent Egg-Hatching Success

Abstract: In the laboratory, we assessed direct effects of electroshock by two types of square‐wave pulsed DC in homogeneous fields of 1.0 peak volts per centimeter on ripe razorback suckers Xyrauchen texanus and evaluated subsequent egg‐hatching success. Four males and four females were exposed for 10 s to a simple 60‐Hz (24% duty cycle) current, and four males and three females were subjected for 10 s to a complex pulse pattern of three 240‐Hz, 2.6‐ms pulses delivered at 15 Hz (12% duty cycle). All shocked fish expell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Finally, the impact on early life stages is also of major concern. Despite several investigators reporting no evidence of harmful effects (Halsband 1967;Halsband and Halsband 1984;Walker et al 1994), others showed that exposure of egg carrying fish to electric fields can cause significant damage or premature expulsion of gametes and sometimes reduced viability of subsequently fertilized eggs (Marriott 1973;Muth and Ruppert 1996;Roach 1996). The survival of embryos on or in the substrate was also affected, particularly when exposure happened between pre-cleavage stages and eyed-egg stages (Godfrey 1957;Lamarque 1990).…”
Section: Harmful Effects On Freshwater Fish Speciesmentioning
confidence: 99%
“…Finally, the impact on early life stages is also of major concern. Despite several investigators reporting no evidence of harmful effects (Halsband 1967;Halsband and Halsband 1984;Walker et al 1994), others showed that exposure of egg carrying fish to electric fields can cause significant damage or premature expulsion of gametes and sometimes reduced viability of subsequently fertilized eggs (Marriott 1973;Muth and Ruppert 1996;Roach 1996). The survival of embryos on or in the substrate was also affected, particularly when exposure happened between pre-cleavage stages and eyed-egg stages (Godfrey 1957;Lamarque 1990).…”
Section: Harmful Effects On Freshwater Fish Speciesmentioning
confidence: 99%
“…Since injuries often heal, injured fish do not necessarily die or suffer long-term physical handicap (Hudy 1985;Schill and Elle 2000). However, survival may be indirectly influenced by the adverse effects of electric shock on behavior, health, and reproductive success (Gatz and Adams 1987;Mesa and Schreck 1989;Muth and Ruppert 1996). These adverse effects have prompted claims that electrofishing may severely affect fish populations (Nielsen 1998), but studies have shown limited or no population-level effects (Schill and Beland 1995;Kocovsky et al 1997;McMichael et al 1998;Carline 2001).…”
mentioning
confidence: 99%
“…However, using prepositioned grid electrofishers in areas of actively spawning fish raises the same concern as other electrofishing techniques. While the effects of electrofishing on fish embryos and larvae are largely unknown (see Snyder 2003 for review), several studies suggest the potential for reduced viability as a result of exposure to electric fields (Godfrey 1957;Lamarque 1990;Muth and Ruppert 1996). Minimizing the affected area and duration of exposure should be top priorities if broodstock collection on active spawning grounds cannot be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Females are generally collected from nearby staging areas after considerable effort. The impact of these repeated passes on the behavior of spawning adults is unknown, but reduced egg viability due to exposure to electric fields has been noted in other species, such as razorback sucker Xyrauchen texanus (Muth and Ruppert 1996), Atlantic salmon Salmo salar (Godfrey 1957), brook trout Salvelinus fontinalis (Godfrey 1957), cutthroat trout Oncorhynchus clarkii (Dwyer and Erdahl 1995), and pink salmon O. gorbuscha (Marriott 1973).…”
mentioning
confidence: 99%